Revolutionizing Fish Tofu Production - Innovations and Quality Insights: Revolusi Produksi Tahu Ikan - Inovasi dan Wawasan Kualitas - Elshiva, Danya Mozza; Azara, Rima; Laksana, Cakra (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the production process of fish tofu, focusing on its use of surimi combined with other ingredients. Through a field internship conducted from September 1 to September 30, 2023, employing observation, interviews, fieldwork, and literature review, the production stages were observed and analyzed. The research aimed to assess whether the process adhered to Good Manufacturing Practice (GMP) standards. Results indicate that the production sequence, including surimi preparation, mixing, molding, boiling, cooling, cutting, frying, freezing, packaging, and storage, aligns with GMP requirements, ensuring product quality and safety. This study fills a gap in understanding fish tofu production processes and provides insights for industry practitioners and researchers aiming to enhance food manufacturing practices and quality control.